Analysis of Structure, the Composition of Vegetation, and Diversity of Epiphytes and Their Hosts - Anthoneta, Y. C. Paiki; Maikel Simbiak; Edoward Krisson Raunsay (Postgraduate, University of Mataram, 2022)
The tourist area of Kali Bak Kampung Harapan Sentani Jayapura Regency is one of the buffer zones for the Cycloop Mountains nature reserve which has the function of a rainwater catchment area and supply of drinking water for the people of Jayapura Regency and City, but currently, the tourist spot is experiencing intensive disturbances and threats. This condition is the reason for this study to be carried out to analyze epiphytic plant vegetation and their hosts in the Kali Bak tourism area, Harapan Sentani Village, Jayapura Regency. The purpose of this study was conducted to determine the structure and composition of the vegetation as well as the diversity of epiphytes and their hosts at the Kali Bak tourist spot, Harapan Sentani Village, Jayapura Regency. Data collection was carried out using transect methods, documentation methods, and plot methods. There are 25 observation plots with a plot size of 20 x 20 meters which are placed on the right and left of the transect line. The results showed that 5 families of 8 species were Asplenium nidus L., Davallia trichomanoides BL., Dendrobium sp, Drynaria quercifolia (L). J.sm., Drynaria rigidula (Sw.).Bedd., Microsorum sp, Microsorum punctatum, and Nephrolepis falcata (Cav.) C. Chr. As for the host tree species, 6 families were obtained consisting of 6 species including Alstonia scholaris (L.) R. Br., Calophyllum inophyllum, Cycas rumphii Miq., Ficus virens Aiton., Gymnostoma papuana Miq., Intsia bijuga (Colebr.) OK. The overall diversity index for epiphytic plants, which is 1.98, is moderate. The overall diversity index for host trees is 1.26 which is moderate